Spontaneous Distal Extrusion of Kuntscher Intramedullary Nail - W. B. Teh; R. Kuharajan; A. H. Noor Shafika; I. G. Nur Azhani (Case Reports in Orthopedics)
Migration of femoral Kuntscher intramedullary nail (K-nail) proximally or distally within the femoral medullary cavity is a well-known documented complication, but spontaneous extrusion of a distally migrated K-nail is a rare complication. This is a case report of a 33-year-old lady who complained of sudden onset left knee pain and presented with spontaneous extrusion of a Kuntscher nail 12 years postinsertion. She underwent a successful K-nail removal surgery and showed a good clinical outcome after 6 months of outpatient follow-up.